Determinants of sub-optimal complementary feeding practices among caregivers of children aged 6–23 months in low-and middle-income countries: scoping review - Makwela, Maishataba Solomon; Mashaba, Reneilwe Given (Frontiers in Public Health, 2025)
Background/ObjectivesLow to middle income countries are burdened by undernutrition and malnutrition mostly affecting children aged < 2 years due to inappropriate feeding practices. Inappropriate feeding practices have been associated with irreversible damage such as stunting and cognitive delays. Therefore, this scoping review aimed to investigate factors that influence sub-optimal complementary feeding practices among caregivers of children aged 6–23 months in low- and middle-income countries. A holistic view of these factors may assist in developing models to prevent inappropriate feeding practices.MethodsThe scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) Checklist.ResultsOne hundred and eight (109) manuscripts were included in the review with a sample size of 1,000,028 caregiver/mother child pairs. Several themes were identified relating to factors that contribute to sub-optimal complementary feeding practices. These included social economic factors, maternal and caregiver's characteristics, child specific factors, cultural and societal influences, health and nutritional services, environment and living conditions, as well as barriers to optimal CF practice.ConclusionsThis scoping review consolidated evidence from a substantial sample of more than one million mother-child pairs from different low- and middle-income countries. The sample size and diversity provide a strong, representative foundation for informing policy, practice, and future research directions. The present study highlighted that feeding practices are affected by multiple factors and that there are interlinks between determinants of sub-optimal CF. These factors of sub-optimal CF and their respective interlinks are different for different locations and should inform future intervention studies and preventative models to better address sub-optimal CF in low to middle income countries.